The Role of the Srikandi Tani 09 Women Farmers Group in Fulfilling the Right to a Healthy Environment - Nurdiyana Nurdiyana; Suanto Suanto; Roni Rustandi; Trisakti Handayani; Sri Rumiati (JUSTISI, 2026)
This study aims to analyze the role of the Srikandi Tani 09 Women Farmers Group (KWT) in realizing the right to a healthy environment as part of the implementation of human rights at the community level in South Tangerang City. This study also identifies the supporting factors and barriers that influence the group’s environmental advocacy activities and examines its contribution to the realization of human rights-based sustainable development. This study employs a qualitative descriptive method, with data collected through interviews, observations, and documentation involving five active members of the PKK organization who participate in KWT activities. The data were analyzed thematically to gain a comprehensive understanding of community-based environmental practices. The novelty of this research lies in its focus on integrating gender empowerment and ecological participation in realizing the constitutional right to a healthy environment, positioned within a human rights perspective. The findings indicate that KWT Srikandi Tani 09 plays an active role in raising environmental awareness, managing limited land for urban agriculture, and processing organic waste into useful materials. The success of these activities is supported by participatory leadership, community solidarity, and collaboration with local government agencies, while challenges arise from limited land, funding, and public environmental awareness. Conclusions from the study indicate that the group’s activities significantly contribute to realizing the right to a healthy environment and the empowerment of women as key actors in sustainable community development.